A numerical tool for modelling oscillating wave surge converter with nonlinear mechanical constraints. (February 2020) - Brito, M.; Canelas, R.B.; García-Feal, O.; Domínguez, J.M.; Crespo, A.J.C.; Ferreira, R.M.L.; Neves, M.G.; Teixeira, L.
Abstract: Mechanical constraints have a non-negligible influence in the motion of oscillating wave surge converter (OWSC) devices. The key novelty of this paper is a numerical simulation tool for OWSCs that does not neglect or significantly compromise mechanical constraints such as hydraulic power take-off (PTO) system, revolute joints and frictional contacts among components. The paper is aimed at presenting the key components of the numerical simulation tool and at validating it with laboratory data featuring an OWSC with mechanical constraints under regular and irregular waves. It is based on the implementation of the multibody solver of Project Chrono under the Smoothed Particle Hydrodynamics (SPH) model of DualSPHysics, where the SPH solver resolves the interaction between wave and flap and the multibody solver resolves the interaction between flap and mechanical constraints. Comparison between numerical results and experimental data show that the numerical simulation tool properly predicts the dynamics of the OWSC. Furthermore, in what concerns hydrodynamics of the near-flap flow, the computed and measured free-surface elevations and phase-averaged flow field show reasonable agreement. Once properly validated, the numerical simulation tool is then applied to study the influence of several mechanical constraints, PTO damping characteristics and flap inertia on the hydrodynamic of the OWSC. The viability of OWSC design solutions based on the developed numerical simulation tool is emphasised, in view of its performance in the test cases to which it was subjected. Highlights: A novel numerical tool for modelling OWSC with mechanical constraints is presented. Dynamic behavior of hydraulic PTO system is implemented. Numerical results are validated through comparisons with new experimental data. Influence of the mechanical constraints and flap inertia are provided.